2019
DOI: 10.3390/insects10080219
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Expertise of the New Jersey Mosquito Control Community to Jump Start Standardized Tick Surveillance

Abstract: Despite the rising incidence of tick-borne diseases (TBD) in the northeastern United States (US), information and expertise needed to assess risk, inform the public and respond proactively is highly variable across states. Standardized and well-designed tick surveillance by trained personnel can facilitate the development of useful risk maps and help target resources, but requires nontrivial start-up costs. To address this challenge, we tested whether existing personnel in New Jersey’s 21 county mosquito contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
(73 reference statements)
0
24
0
Order By: Relevance
“…During the 2018 NJ Tick Blitz, ticks were collected across all 21 NJ counties by sweeping the vegetation along 300-m transects during the morning of May 10, 2018. 25 Ecotonal areas were chosen to target D. variabilis, including open grassland or meadows adjoining forest or woodland, prime habitat for the meadow vole (Microtus pennsylvanicus), 26 the preferred host of larval and nymphal D. variabilis. 27 As described, 25 to simplify the process for firsttime tick collectors, we provided volunteers from each county mosquito control program with a lightweight collapsible "tick sweep" made of 0.25 m 2 crib flannel (buybuy Baby, Union Township, NJ) with a PVC pipe handle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 2018 NJ Tick Blitz, ticks were collected across all 21 NJ counties by sweeping the vegetation along 300-m transects during the morning of May 10, 2018. 25 Ecotonal areas were chosen to target D. variabilis, including open grassland or meadows adjoining forest or woodland, prime habitat for the meadow vole (Microtus pennsylvanicus), 26 the preferred host of larval and nymphal D. variabilis. 27 As described, 25 to simplify the process for firsttime tick collectors, we provided volunteers from each county mosquito control program with a lightweight collapsible "tick sweep" made of 0.25 m 2 crib flannel (buybuy Baby, Union Township, NJ) with a PVC pipe handle.…”
Section: Methodsmentioning
confidence: 99%
“…25 Ecotonal areas were chosen to target D. variabilis, including open grassland or meadows adjoining forest or woodland, prime habitat for the meadow vole (Microtus pennsylvanicus), 26 the preferred host of larval and nymphal D. variabilis. 27 As described, 25 to simplify the process for firsttime tick collectors, we provided volunteers from each county mosquito control program with a lightweight collapsible "tick sweep" made of 0.25 m 2 crib flannel (buybuy Baby, Union Township, NJ) with a PVC pipe handle. Participants removed ticks from the sweep with masking tape and placed the tape inside plastic Ziploc (SC Johnson, Racine, WI) bags with a small piece of wet paper towel to keep ticks alive until they were brought to the Rutgers Center for Vector Biology by a courier later that week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-functioning mosquito management programs are based on the principles of integrated pest management (striving to protect the human population from mosquito bites and mosquitoborne disease agents while at the same time minimizing the impact of pesticides on the environment) and staffed with professionals experienced in public outreach, mosquito biology, pesticide use, and operational surveillance and control concepts. Expanding the activities of existing mosquito management programs to also include ticks (50) provides an economy of scale compared with the alternative of having separate community-supported mosquito-and tick-management programs. Specific benefits from building tick responsibilities into an existing mosquito management program might include shared use of existing office/laboratory space, laboratory equipment, and vehicles; presence of professionals already skilled in morphologic vector identification and knowledgeable about basic principles for vector surveillance and control; presence of licensed and highly experienced pesticide applicator personnel; and presence of personnel with previous experience of public outreach for vector-related issues.…”
Section: Need For Local and Professionally Staffed Integrated Tick-mamentioning
confidence: 99%
“…An example of keen a priori surveillance planning to achieve an objective can be found in the study by Egizi et al [17]. While acknowledging that active surveillance requires funding and infrastructure that most agencies lack, these authors harnessed the infrastructure that New Jersey has in place for vector control, the New Jersey mosquito control community, and demonstrated that with minimal resource investment, they could perform a standardized tick survey for an understudied and underappreciated disease vector, Dermacentor variablis .…”
Section: The Science Of Surveillance and Its Applicationmentioning
confidence: 99%